CeO2-TiO2 Photocatalyst: Ionic Liquid-Mediated Synthesis, Characterization, and Performance for Diisopropanolamine Visible Light Degradation - Jagath Retchahan Sivalingam; Fai Kait Chong; Cecilia Devi Wilfred (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
CeO2-TiO2 photocatalyst with Ce:Ti molar ratio of 1:9 was synthesized via co-precipitation method in the presence of 1-ethyl-3-methyl imidazolium octylsulfate, [EMIM][OctSO4] (CeO2-TiO2-IL). The ionic liquid acts as a templating agent for particle growth. The CeO2-TiO2 and TiO2 photocatalysts were also synthesized without any ionic liquid for comparison. Calcination was conducted on the as-synthesized materials at 400˚C for 2 h. The photocatalysts were characterized using diffuse reflectance UV-Vis spectroscopy (DR-UV-Vis), field emission scanning electron microscopy (FESEM), X-ray powder diffraction (XRD), and surface area and pore size analyzer (SAP). The presence of CeO2 has changed the optical property of TiO2. It has extended the absorption edge of TiO2 from UV to visible region. The calculated band gap energy decreased from 2.82 eV (TiO2) to 2.30 eV (CeO2-TiO2-IL). The FESEM morphology showed that samples forms aggregates and the surface smoothens when ionic liquid was added. The average crystallite size of TiO2, CeO2-TiO2, and CeO2-TiO2-IL were 20.8 nm, 5.5 nm, and 4 nm. In terms of performance, photodegradation of 1000 ppm of diisopropanolamine (DIPA) was conducted in the presence of hydrogen peroxide (H2O2) and visible light irradiation which was provided by a 500 W halogen lamp. The best performance was displayed by CeO2-TiO2-IL calcined at 400˚C. It was able to remove 82.0% DIPA and 54.8% COD after 6 h reaction.